2015
DOI: 10.3945/jn.114.198366
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Status at Age 3 Months Is Associated with Adiposity and Cardiometabolic Markers at Age 4 Years in Mexican Children

Abstract: EBF and PreBF at 3 mo were associated with lower adiposity and serum total cholesterol in children at 4 y. In addition, BF >12 mo was associated with lower adiposity. These data confirm the importance of exclusive BF and prolonged BF for later cardiometabolic health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
4
14
0
6
Order By: Relevance
“…Likewise continued breastfeeding (CBF) for over 12 months was associated with lower adiposity. These data support the importance of EBF and CBF for later cardiometabolic health (8) .…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Likewise continued breastfeeding (CBF) for over 12 months was associated with lower adiposity. These data support the importance of EBF and CBF for later cardiometabolic health (8) .…”
Section: Introductionsupporting
confidence: 77%
“…Obesity is on the rise and is a significant public health problem in the EMR, where one half of the countries have the highest rates of obesity in the world. Breastfeeding is protective against later obesity (8) . Also exclusive breastfeeding (EBF) was found to be associated with lower adiposity and serum total cholesterol in children at 4 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…52,53 A prospective study on Mexican children concluded that an exclusive and prolonged breastfeeding had a beneficial effect on later cardiometabolic health through lower total cholesterol, lowdensity lipoprotein (LDL) cholesterol and triglycerides levels at the age of 4. 54 Some studies demonstrated that these lower levels persisted even later in adulthood (from 17 to 64 years). 55 Yet, earlier at 4 and 8 weeks of life, formula-fed infants had lower serum cholesterol, triglyceride and transaminase level (ALAT, ASAT, γGT) compared with breastfed infants.…”
Section: Cardiovascular Risks Factorsmentioning
confidence: 99%
“…This susceptibility to adult chronic diseases may be a response to exposures in utero —known as fetal programming—or early malnutrition in extra uterine life ( 224 , 225 ). Several studies in Latin America have documented the inverse association between BW and insulin sensitivity later in life ( 226 ), malnutrition during the first year of life and insulin sensitivity, glucose tolerance and metabolic syndrome later in life ( 227 229 ); and being exclusively or predominantly breastfed > 12 months and lower adiposity and serum cholesterol during childhood ( 230 ).…”
Section: Etiology Of Type 2 Dm In Hispanics/latinosmentioning
confidence: 99%